The Regional Econetwork Of Vinnitsya Region - Яцентюк, Ю. В. (Man and Environment. Issues of Neoecology, 2014)
The features of Vinnytsya region еcоnеtwork are described. The national core areas, regional centres of biotic diversity, national and regional еcоlogical corridors of Vinnytsya oblast are considered. The structure of the ecological network Vinnytsia region identified 41 key territory. Among them are three national parks kernel and 38 regional centers of biodiversity. They differ most biological and landscape diversity and generally represented nature reserves.